Effect of grain source and 0 or 4% added fat on performance of finishing pigs - Allee, G.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Seventy-two crossbred finishing pigs averaging 55.9 kg. (123.0 lbs.) were used (in a 3 x 2 factorial design) to compare performance when fed sorghum, corn, or wheat with 0 or 4% added fat (tallow). There were no significant differences in average daily gain or feed efficiency among pigs fed sorghum, corn, or wheat. Adding 4% fat (to each grain ration) resulted in a slight improvement in gain and an improved feed efficiency. Pigs fed wheat with 4% fat added showed The greatest improvement in daily gain and feed efficiency.
Bright Future? is known as Swine Day, 1977
Keywords: Swine; Grain; Fat; Performance; Finishing pigs; Tallow